Analisis Preferensi Konsumen terhadap Buah Semangka di Pasar Tradisional Kota Denpasar - PERDANI, I GUSTI AYU KIRANA TATA; AMBARAWATI, I GUSTI AGUNG AYU; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022DO - 10.24843/JAA.2022.v11.i01.p39, 2022)
Analysis of Consumer Preferences on Watermelon at Traditional Markets in Denpasar City . Watermelon is a fruit commodity that is available throughout the year, which could be found at traditional markets, modern markets, and fruit retailers. This study aims to determine the consumer preferences attributes of watermelon and to find out the attributes that are most considered by consumers. The types of data used in this research are quantitative and qualitative data. Sources of data used in this study are primary and secondary data. Chi-square analysis was used to determine consumer preferences for watermelon attributes and Fishbein multi-attribute was used to determine the attributes most considered by consumers. The watermelon attributes studied were price, color, size and shape. The research location was chosen purposively by selecting four traditional markets. 80 samples were selected by using accidental sampling technique. The results of the Chi-square analysis indicate that there is a preference relationship between the four attributes studied. Attributes that become consumer preferences are round shape, red color, medium size (3-5 kg) and medium price (IDR 15,000-20,000 per kg). The result of Fishbein's multi-attribute analysis shows that the attribute most considered by consumers is shape. Marketers should further increase the supply of medium sized watermelons (3-5 kg) in order to meet consumer preferences. Producers can increase the production of medium-sized watermelons by selecting superior seeds, treating them, and cultivating land and irrigation.